CRITICAL-POINT YIELD MODEL TO APPRAISE DAMAGE CAUSED BY LEAF BLIGHT IN BEAN CROP - Garcés Fiallos, Felipe Rafael (2011)
In Ecuador, the bean (Phaseolus vulgaris L.) is consumed by the population majority, and also a source of income for small and medium producers. One of the most important disease is the blight or root rot rhizoctonia, caused by the necrotrophic fungus Rhizoctonia solani Kuhn (teleomorph Thanatephorus cucumeris Frank). The objective was to determine the reduction in grain yield caused by natural infection of leaf blight disease in different cultivars of beans, the crop year 2010, the city of Quevedo, Ecuador. The experimental design was randomized blocks with seven treatments and four replicates, which were used to generate gradients of disease, while having the genetic variability among the materials. The assessment of severity (% leaf area necrotic.plot-1) of the disease was in the R7 growth stage (pod development). The crop was harvested at the 124 days post-seeding, to quantify the yield. The equation of the damage function obtained was R = 4,257.50 to 33.16 S, where R is yield and S is the severity (%) of the disease, with R2 = 0.82 and P<0.0001. With the resulting equation was normalizes to 1,000 kg, which is R = 1,000.0 to 7.79 S. It was concluded that the generated damage equation can be used to calculate the economic damage threshold (EDT), which is an alternative indicator of the time for application of chemical control of blight on susceptible cultivars, while maintaining the profitability of the farmer and be friendly with the environment.